2014 Asia-Pacific Conference on Computer Aided System Engineering (APCASE) 2014
DOI: 10.1109/apcase.2014.6924484
|View full text |Cite
|
Sign up to set email alerts
|

A cloud-based mobile robotic system for environmental monitoring

Abstract: Cloud computing is one of the major emerging technologies of the early 21st century, and has the potential to boost socio-economic development significantly. While cloud computing has traditionally meant software technology, of late there has been active research on cyber-physical cloud systems involving vehicles and mobile robots. In this paper, a set of mobile field robots linked by wireless communication is connected to a cloud server for the purpose of environmental monitoring. One of the robots is used as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…IAQ monitoring is a trending topic for which some other low-cost and open-source monitoring systems have been developed [43][44][45][46][47][48][49]. Due to the quality and relevant contribution of these solutions, a brief summary of these studies is presented in The RSSI test at floor level showed that the maximum distance between nodes was 8 m. The RSSI test at 1 m height reported 3 to 5 m distance.…”
Section: Discussion and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…IAQ monitoring is a trending topic for which some other low-cost and open-source monitoring systems have been developed [43][44][45][46][47][48][49]. Due to the quality and relevant contribution of these solutions, a brief summary of these studies is presented in The RSSI test at floor level showed that the maximum distance between nodes was 8 m. The RSSI test at 1 m height reported 3 to 5 m distance.…”
Section: Discussion and Resultsmentioning
confidence: 99%
“…A set of mobile robots connected via Wi-Fi to a cloud server to provide environmental supervision is proposed by [48]. The master robot is configured as a base station, while the others are configured as sensor nodes that are responsible for the data acquisition and for transmitting the collected data to the base station.…”
Section: Related Workmentioning
confidence: 99%
“…A system containing mobile robots for environmental supervision was proposed by [99]. It was connected to the cloud server wirelessly.…”
Section: Indoor Air Quality Monitoring: Architectures Algorithms and ...mentioning
confidence: 99%